The Evaluation of Genetic Diagnosis on High-Risk Fetal CAKUT - Liu, Wanlu; Shi, Xinwei; Li, Yuqi; Qiao, Fuyuan; Chen, Suhua; Feng, Ling; Zeng, Wanjiang; Deng, Dongrui; Wu, Yuanyuan (Frontiers in Genetics, 2022)
Background: It is challenging to make an accurate prenatal diagnosis for congenital anomalies of the kidney and urinary tract (CAKUT) because of its pathologic diversity. This study aims to evaluate the performance of whole-exome sequencing (WES) combined with karyotype analysis and copy number variations (CNVs) in diagnosing high-risk fetal CAKUT. Methods: We conducted a retrospective study on prenatal diagnoses of CAKUT in our hospital from January 2020 to April 2021. The research studied 24 high-risk fetuses with CAKUT who were scanned by ultrasonography at the prenatal diagnosis center of Tongji Hospital affiliated to Tongji Medical College of Huazhong University of Science and Technology. The likely pathogenic gene variants were screened for the patients and their parents by multiple approaches, including karyotype analysis, CNVs and WES, and further verified with Sanger sequencing. Results:①We detected abnormal CNVs in 20.8% (5/24) of the fetuses but only 8.3% (2/24) fetuses had abnormal karyotypes. ②Of the 15 CAKUT fetuses, positive findings (40%) were detected by WES. Of the 9 high-risk fetuses with CAKUT (negative findings in ultrasound scan but with family history), we found abnormal variants (77.8%) through WES. Conclusion: The application of CNVs and WES showed advance in prenatal diagnosis of CATUK and the pathogenic gene variants were detectable especially for high-risk fetuses with negative ultrasound findings on CAKUT in the preliminary study. The applied strategy could be used to improve the accuracy of prenatal diagnosis for CAKUT in the future.